2023
DOI: 10.1116/6.0002393
|View full text |Cite
|
Sign up to set email alerts
|

NiO/β-(AlxGa1−x)2O3/Ga2O3 heterojunction lateral rectifiers with reverse breakdown voltage >7 kV

Abstract: NiO/β-(Al xGa1− x)2O3/Ga2O3 heterojunction lateral geometry rectifiers with diameter 50–100  μm exhibited maximum reverse breakdown voltages >7 kV, showing the advantage of increasing the bandgap using the β-(Al xGa1− x)2O3 alloy. This Si-doped alloy layer was grown by metal organic chemical vapor deposition with an Al composition of ∼21%. On-state resistances were in the range of 50–2180 Ω cm2, leading to power figures-of-merit up to 0.72 MW cm−2. The forward turn-on voltage was in the range of 2.3–2.5 V, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…While UWBG devices have not reached 10 kV, gallium oxide (Ga2O3) is approaching. Breakdown voltage (BV) from 3 kV up to 8.56 kV has been reported in Ga 2 O 3 -based lateral [5], [6] and vertical diodes [7]- [11] as well as lateral MOSFETs [12]- [15]. Additionally, the availability of highquality 4-inch wafers [16] and the reports of high-performance packaging, device robustness, and converter applications [17] all consolidate the promise of Ga2O3 for power electronics.…”
Section: Introductionmentioning
confidence: 93%
“…While UWBG devices have not reached 10 kV, gallium oxide (Ga2O3) is approaching. Breakdown voltage (BV) from 3 kV up to 8.56 kV has been reported in Ga 2 O 3 -based lateral [5], [6] and vertical diodes [7]- [11] as well as lateral MOSFETs [12]- [15]. Additionally, the availability of highquality 4-inch wafers [16] and the reports of high-performance packaging, device robustness, and converter applications [17] all consolidate the promise of Ga2O3 for power electronics.…”
Section: Introductionmentioning
confidence: 93%
“…Figure 10d shows the reverse I-V characteristics of the devices, where the negative temperature dependence of the BVs was observed, and thus the breakdown mechanism did not involve avalanche breakdown. They further studied devices with different diameters (50, 75, and 100 µm) [103]. The forward I-V curves of the devices with different diameters showed that the inclusion of the alloy did not significantly degrade the turn-on voltage.…”
Section: β-(Almentioning
confidence: 99%
“…Masten et al used a similar approach to fabricate β-(AlxGa1−x)2O3/β-Ga2O3 metal-semiconductor field effect transistors with promising performance (22). We have previously shown that such structures may reach high breakdown voltages, around 7 kV, but have relatively high on-resistance (45).…”
Section: Introductionmentioning
confidence: 99%